Research of Flipped Classroom based on Students’ Perceptions - Kazu, İbrahim Yasar; Kurtoğlu, Cemre (Asian Journal of Education and Training, 2020)
Research of flipped classroom can be carried out in such dimensions as teacher, school manager, parents and students. This present research is aimed to investigate the secondary school students’ flipped classroom readiness. The survey method was applied in this descriptive study. ‘A Scale for Flipped Classroom Readiness of Secondary School Students’ was applied as developed by Hao and adapted by Durak. The scale was applied to 383 5th grade and 362 8th grade totally 745 students studying at five different secondary schools which were chosen randomly from city center of Elazig. Obtained data were analysed using SPSS Program Version 22.0. Their readiness for flipped classroom learning was investigated in five sub dimensions: ‘self-directed learning, technology self-efficacy, in-class communication self-efficacy, motivation for learning and doing preview’. Their flipped classroom readiness was found positive in general. Students who have a computer and those who perceive themselves competent at using technological devices have more positive opinions on the flipped classroom.